PENGARUH PEMAHAMAN AKUNTANSI DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN (Survey pada SKPD Kota Lhokseumawe) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
This study aims to examine influence the understanding of accounting and regional financial accounting system on the quality of financial statements at SKPD Kota Lhokseumawe. The data used in this study are primary data by dividing questionnaires to 114 respondents used as research samples. Data processing is done through multiple linear equations model. The result of research shows that: In partial, the understanding of accounting has influence not significant on the quality of financial statements at SKPD Kota Lhokseumawe and regional financial accounting system have a significant effect on the quality of financial statements at SKPD Kota Lhokseumawe. Simultaneously the understanding of accounting and financial accounting system has significant effect on the quality of financial statements at SKPD Kota Lhokseumawe. Understanding the accounting and financial accounting system of the region has a strong relationship with the quality of financial statements at SKPD Lhokseumawe. Understanding of accounting and financial accounting system of area have ability in explaining influence to quality of financial report at SKPD Kota Lhokseumawe.